Study of geotextiles in the treatment of wastewater from farming rainbow trout (Oncorhynchus mykiss) (Orinoquia, 2017)
The process of production of the fish farms generate two types of effluents: one with continuous flow during normal operation and the other an intermittent flow during cleaning operations. This last one has a lot higher solid concentration than the normal operation effluent. The present study was designed to assess at laboratory scale, the non woven geotextile filtration for the treatment of cleaning effluents from a MULTIPRO pond with rainbow trout (Oncorhynchus mykiss) culture. The efficiency in the reduction of suspended material, nutrients and organic matter was evaluated, as well as the development of the hydraulic head losses. It was determined that the filtration of these effluents through non woven geotextiles allows to obtain the following average removal efficiencies: total suspended Solids (98%), biochemical oxygen demand (68%), total phosphorus (62%) and total Kjeldahl nitrogen (79%) at filtration rate of 3 m/h. These efficiencies are comparable or even higher than those reported by higher-cost technologies, which would present limitations for rural use in Colombia. It was observed a rapid development of head loss and consequently low filter run duration with an average value of 39 min. This is suggesting that non woven geotextile filtration should be optimized en terms of filter run duration, so as to allow a more extended use of the blankets and to reduce the investment costs associated to the replacement of the same ones.
Keywords: Wastewater aquaculture; MULTIPRO pond; filtration; non woven geotextiles